ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT TERHADAP PRODUK GADAI KREDIT CEPAT AMAN (KCA) DI NGANJUK - Dzakwan, Naufal Adhwa' (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2025)
Due to the difficulty of families finding a livelihood to support their economy, they must continue to improve their quality of life in various ways. At this point, PT Pegadaian provides various solutions to make it easier for people when they need funds quickly, safely, and easily. This study aims to analyze the factors influencing public interest in the Fast Secure Credit (KCA) pawn product at PT Pegadaian UPC Warujayeng Nganjuk East Java. The researcher used quantitative research with a case study type. The results of the study showed that there were several factors that influenced public interest in the KCA Pawn product at PT Pegadaian UPC Warujayeng, including product quality, promotion, service quality, customer satisfaction, location, and knowledge. Not only that, the most dominant factor influencing public interest in the Pawn product at UPC Warujayeng is the quality of the service itself.